Gender differentiated vulnerability to climate change in Eastern Uganda. (26th November 2019) - Balikoowa, Kenneth; Nabanoga, Gorettie; Tumusiime, David Mwesigye; Mbogga, Michael S.
ABSTRACT: Climate change literature is rife with the assertion that women are more vulnerable to climate change, which state is expected to reflect on female-headed households. However, this assertion has however not been empirically proven aside from the general poverty-gender linkages. This study used primary data collected in 2016 from 735 randomly selected households from four districts in Eastern Uganda to construct a gender vulnerability index to compare and explain the drivers of vulnerability between male and female-headed households. The results show that female-headed households were more vulnerable (GVI-IPCC = −0.134) than male-headed households (GVI-IPCC = −0.176). The results further show that disparity in adaptive capacity mediates vulnerability between male and female-headed households. This underscores the importance of proactive interventions rather than protectionist approaches to reducing vulnerability. The study has extended the analytical utility of the livelihood vulnerability index to create a gender vulnerability index for comparing contextual groups of households in Eastern Uganda.